REVEALING THE ROLE OF PROFITABILITY IN MEDIATING LEVERAGE, LIQUIDITY, AND COMPANY SIZE ON FIRM VALUE IN HEALTH SECTOR - Adisty, Fairuznissa Pelita; Mardi; Ulupui, I Gusti Ketut Agung (Faculty of Economics and Business, Universitas Negeri Jakarta, 2024)
The purpose of this study is to examine the impact of leverage, liquidity, and firm size on firm value with profitability as a mediating variable. The unit of analysis is healthcare companies listed on the Indonesia Stock Exchange for the period 2020-2023. The research method used is quantitative method using secondary data. Research data taken from financial and annual reports totaling 33 companies. The sample amounted to 22 companies with a total of 88 sample data with purposive sampling as a sampling technique. Data analysis using path analysis and using the SPSS version 25 application. Based on the research results obtained that leverage has no effect on firm value and liquidity has no effect on firm value, while company size has a positive and significant effect on firm value and profitability has a positive and significant effect on firm value. Profitability is proven to be able to mediate the relationship between liquidity and firm value, but profitability is unable to mediate the relationship between leverage and firm value and profitability is unable to mediate the relationship between firm size and firm value.